Life Skills Education Program: Is it Beneficial for the Society? - Mulyadi, Didi; Suryadi, Suryadi; Aliyyah, Rusi Rusmiati (Journal of Nonformal Education, 2020)
The life skills education program was created to answer the poverty and unemployment problems faced by those without access to formal education. The research is aimed at evaluating the implementation effectiveness of the life skills education program at the Course and Training Institutions. This research uses the qualitative approach with the evaluative method. The evaluation model used is a model developed by Stufflebeam, namely CIPP model (context, input, process, product) but this article only focuses on the product evaluation. The results of this study indicate that the result of the program did not run as expected as the program partcipants absorped by formal employment nly numbers 18% while the others were only working as part times employment. The result also recommend that the program developer needs a very careful judgement when choosing the Course and Training Institutions executing the program. The research at the product stage showed that most of the program alumni don’t enter to formal sector. The novelty and contribution of this research is the creation of an evaluation model using the AIR method (Achievements, Issues and Recommendations) which will facilitate further researchers and related parties in utilizing the results of this study.